The role of sp2 and sp3 hybridized bonds on the structural, mechanical, and electronic properties in a hard BN framework. Issue 5 (21st January 2019) - Bu, Hongxia; Zheng, Haibin; Zhou, Hongcai; Zhang, Hongyu; Yang, Zaifa; Liu, Zhie; Wang, Hui; Xu, Qi
Abstract : A first-principles approach is used to systematically investigate the role of sp 2 and sp 3 hybridized bonds on the structural, mechanical, and electronic properties in a new BN phase (denoted Hex-(BN)12 ). Abstract : A first-principles approach is used to systematically investigate the role of sp 2 and sp 3 hybridized bonds on the structural, mechanical, and electronic properties in a new BN phase (denoted Hex-(BN)12 ). Hex-(BN)12 has the same number of sp 2 and sp 3 hybridized atoms. The calculated cohesion energy, phonon frequencies, and elastic constants unambiguously confirm the structural stability of this compound. Due to the different types of hybridization and B–N covalent bonds with ionic characteristics, Hex-(BN)12 has unequal bond lengths and bond angles in these hybrid orbitals. These cause the relative energetic stability to be slightly lower than c-BN and w-BN. The hardness of Hex-(BN)12 is estimated to range from 33 to 40 GPa. The bond-breaking order under stress is sp 3 –sp 3, sp 2 –sp 3, and sp 2 –sp 2 . DFT calculations with the gradient approximation (GGA) and HSE06 functional indicate the electronic structure contains an indirect band gap at 3.21 and 4.42 eV, respectively. The electronic states in the region near the Fermi level primarily arise from the 2p orbitals in sp 2 -hybridized atoms. In general, sp 3 bonded B and N atoms guarantee higher mechanical properties, and sp 2 bonded atoms ensure ductility and even conductivity, although all changes vary with spatial structure. Hex-(BN)12 can be obtained from multilayer yne-BN, and BN nanosheets, nanotubes and nanoribbons under pressure.